Call For Book Review Editor - Christou, Theodore; DeLuca, Christopher (Journal of the Canadian Association for Curriculum Studies, 2014)
The Journal of the Canadian Association for Curriculum Studies (JCACS) is currently inviting applications for the position of Book Review Editor. The position begins in January 2015. The call for applications will remain open until July 1, 2014.